2020
DOI: 10.1186/s12974-020-01893-3
|View full text |Cite
|
Sign up to set email alerts
|

Muramyl dipeptide-mediated immunomodulation on monocyte subsets exerts therapeutic effects in a mouse model of Alzheimer’s disease

Abstract: Background: Muramyl dipeptide (MDP) is a component derived from minimal peptidoglycan motif from bacteria, and it is a ligand for the NOD2 receptor. Peripheral administration of MDP converts Ly6C high into Ly6C low monocytes. Previously, we have shown that Ly6C low monocytes play crucial roles in the pathology of a mouse model of Alzheimer's disease (AD). However, medications with mild immunomodulatory effects that solely target specific monocyte subsets, without triggering microglial activation, are rare. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The study has shown a delayed cognitive decline associated with a stable increase in patrolling monocytes and a drastic diminution of inflammatory monocytes in the blood over time. Interestingly, the effect of repeated injections of MDP was still effective in six-month-old mice and we did not find health issues suggesting that the molecule is safe in mice even for three consecutive months [151]. These results also suggest that the cognitive improvement in the MDP group could be attributed to the sink effect since MDP-injected mice presented a higher expression level of LRP.…”
Section: Mdpsupporting
confidence: 55%
See 2 more Smart Citations
“…The study has shown a delayed cognitive decline associated with a stable increase in patrolling monocytes and a drastic diminution of inflammatory monocytes in the blood over time. Interestingly, the effect of repeated injections of MDP was still effective in six-month-old mice and we did not find health issues suggesting that the molecule is safe in mice even for three consecutive months [151]. These results also suggest that the cognitive improvement in the MDP group could be attributed to the sink effect since MDP-injected mice presented a higher expression level of LRP.…”
Section: Mdpsupporting
confidence: 55%
“…This receptor is able to transport amyloid through the blood-brain barrier and, interestingly, LRP1 expression is downregulated in AD [153,154]. The cognitive improvement is also associated with a higher expression of the synaptic marker PSD-95 compared to APP mice at six months [151]. Altogether, these results demonstrated a strong beneficial role of MDP in AD, but further studies are needed to unveil the underlying mechanisms.…”
Section: Mdpmentioning
confidence: 88%
See 1 more Smart Citation
“…The second subset is known for alternative and non-classical activation, and it is characterized by an antiinflammatory phenotype and CX3CR1-dependent recruitment to local non-inflamed tissues; this subpopulation expresses Ly6C − CCR2 low CX3CR1 high markers (28)(29)(30). Blood monocytes have plasticity and are embroiled in pro-inflammatory and antiinflammatory responses in various diseases (28,(31)(32)(33)(34). Blood monocytes are a heterogeneous population of circulating leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that TLR-2 and NOD2 may play a relevant role in neuroinflammation and AD. On the other hand, the intraperitoneal administration (10 mg Kg −1 once or twice weekly) for three or six months of muramyl dipeptide (MDP), a NOD2 receptor ligand, to 3-month-old APP swe /PS1 transgenic male mice and, as controls, to age-matched C57BL/6J mice was beneficial under several respects with no concurrent microglial activation in both earlier and later phases of the neuropathology in AD-model mice [280].…”
Section: Nod Inflammasomesmentioning
confidence: 99%